Father's Involvement in Sex Education for Children in Muslim Minority Countries - Azam Syukur Rahmatullah; Dewi Sekar Kencono; Mohd Sukki Othman; Muhammad Suyudi; Akbar Nur Aziz (Jurnal Pendidikan Agama Islam, 2024)
Purpose – To analyze how fathers are involved in educating their children about sex and morality in countries with Muslim minorities. Design/methods/approach – The research is a field study located in Australia, specifically in Sydney and Melbourne. The approach used is phenomenology, which seeks to understand the essence of human experience sequentially from the perspective of the participants as the first informants. There are six informants, three from Sydney and three from Melbourne, all of whom are Indonesian citizens who have been permanent residents and have lived in Australia for around 23-43 years. Findings – The results show that fathers, who are central figures, have morals, positive changes, and wisdom and have several techniques for educating their children about sex. First, building self-awareness in children from an early age to always be careful in their behaviour; second, building intensive interaction and communication with the unborn child in the mother's womb in an effort to instil positive values in the unborn child; third, strengthening the child's spiritual side from an early age; fourth, building a culture of shame in children from an early age. Research implications/limitations - This research implies that the role of fathers in the sexual and moral education of children in countries with Islamic minorities is very important in ensuring that Islamic values remain integrated into the moral development of children, even in environments dominated by a different majority culture. Originality/value – This research provides new insights into how fathers in countries with Muslim minorities actively and strategically overcome cultural and religious challenges in providing sexual and moral education to their children.